Depression and quality of life of hemodialysis patients living in a poor region of Brazil - Santos,Paulo Roberto (2011)
OBJECTIVE: To determine the correlation between depression and quality of life (QOL) of patients in hemodialysis (HD). METHOD: One hundred and sixty six patients over 18 years of age who had been in HD for at least three months and had no history of transplant. QOL was assessed using the SF-36. To categorize depression, a score > 10 was used on the 10-item version of the Center for Epidemiologic Studies Depression Scale (CES-D). Comparisons between depressed and nondepressed patients were performed using the chi-square test, Student's t-test, and Mann-Whitney test. Multiple regression was performed to assess the predictive variables of patients' QOL. RESULTS: Symptoms of depression were found in 13 (7.8%) patients. The only variable that differed among depressed patients was QOL. Depressed patients presented lower scores in vitality (40.7 vs. 57.3; p = 0.010), role-emotional (25.6 vs. 62.5; p = 0.006), and mental health (50.1 vs. 65.4; p = 0.023). Regression analysis demonstrated that depression was a predictor of role-emotional (OR = 0.981, CI = 0.967-0.996; p = 0.010) and mental health (OR = 0.970, CI = 0.946-0.996; p = 0.022). CONCLUSION: Depressed patients experience a poor QOL because, in addition to their chronically affected physical aspects, they also feel limited in the mental dimensions, which usually have the highest score among non-depressed HD patients.